2001
DOI: 10.1103/physreve.64.056214
|View full text |Cite
|
Sign up to set email alerts
|

Whispering gallery modes in open quantum billiards

Abstract: The physics of nanoscale systems has advanced rapidly over the last few years. A consistent description of these small systems is a challenging task for quantum theory since their properties may be influenced strongly by attaching leads to them [1][2][3][4][5][6][7][8][9]. They are simulated often by means of quantum billiards. When the cavity is not fully opened, the propagation of the mode is restricted to energies at which the overlap integral between the wave functions of the resonance states and the chann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 19 publications
(26 reference statements)
8
67
0
1
Order By: Relevance
“…For transport through open chaotic systems, classical ergodicity clearly has to be established faster than the lifetime of an electron in the system. Accordingly, the dynamics should not allow for too many short, nonergodic classical scattering trajectories going straight through the cavity, or hitting its boundary only very few times [25]. This requires that the inverse Lyapunov exponent λ −1 and the typical time τ B between bounces off the confinement are much smaller than the dwell time τ D , hence λ −1 , τ B ≪ τ D .…”
Section: Introductionmentioning
confidence: 99%
“…For transport through open chaotic systems, classical ergodicity clearly has to be established faster than the lifetime of an electron in the system. Accordingly, the dynamics should not allow for too many short, nonergodic classical scattering trajectories going straight through the cavity, or hitting its boundary only very few times [25]. This requires that the inverse Lyapunov exponent λ −1 and the typical time τ B between bounces off the confinement are much smaller than the dwell time τ D , hence λ −1 , τ B ≪ τ D .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental studies on open microwave cavities and also on quantum dots at low energy have shown that the individual properties of the states and their matching to the wave functions of the environment play an important role, indeed [8,9,[15][16][17][18]. Analytical considerations show that level repulsion as well as level clustering may appear.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the matching of the wave functions for the dynamics of the system is studied further in [17]. Here, some special states are shown to accumulate the total coupling strength between system and environment which is expressed by the sum of the widths of all states lying in the energy region considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both time scales are well separated from one another. A theoretical example are the shortlived whispering gallery modes in a small microwave cavity with convex boundary which coexist with many long-lived states, for details see [20][21][22]. An experimental example are the isobaric analogue resonances in medium -mass nuclei.…”
Section: Resonance Trapping and Dynamical Phase Transitionsmentioning
confidence: 99%